Psychometric analysis of the Feminism and Women’s Movement Scale in cisgender LGB youth from Lima, Peru - Carranza Benites, Renzo (Acta Universitaria, 2026)
Attitudes regarding feminism and women’s movements have gained relevance in cisgender LGB youth, although there are still few validated instruments to assess these attitudes. The purpose of the research was to carry out the validation of the psychometric properties of the Feminism and Women’s Movement (FWM) Scale in the cisgender LGB community, an instrument designed to measure attitudes towards feminism. It was conducted under an instrumental design, which allows evaluating the potential and reliability of psychometric instruments. The population studied was composed of members of the cisgender LGB community, achieved using the snowball sampling technique, which facilitated the inclusion of those who had relevant experiences. It was found that the FWM possesses a unidimensional structure with acceptable indicators of fit, is reliable, and has relationship to flourishing.